Amputation Risk in Type II Diabetes Mellitus Patients Treated with SGLT-2 Inhibitors: A Systematic Literature Review of Randomized Clinical Trials - Hoda, Farazul; Jamali, Mohammad Chand; Arshad, Mawrah; Habib, Mohammad Anwar; Akhtar, Mohd; Najmi, Abul Kalam (Drug Research, 2024)
Background SGLT-2 inhibitors, prescribed for type 2 diabetes, have a heightened risk of amputation. The FDA issued a warning in May 2017, leading to the inclusion of a cautionary label. Vigilance is essential for patients and healthcare providers to promptly identify and address potential limb complications associated with the use of SGLT-2 inhibitors.Method A comprehensive search of electronic databases was conducted, covering the period from inception to May 2024. This systematic literature review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The quality of the included studies was assessed using the Cochrane risk of bias (ROB) tool. Inclusion and exclusion criteria were predefined, and data extraction was performed to summarize the findings.Result A total of 12 randomized control trial (RCT) studies were included in the present systematic review. 37,657 (54.89%) participants were randomly assigned to receive the different interventions of SGLT-2 inhibitor, whereas 30,959 (45.11%) received a placebo. Overall, 618 events were reported in the treatment group, whereas 396 events were reported in the placebo group.Conclusion In conclusion, patients treated with SGLT-2 inhibitors did not have any significant difference in amputation occurrences compared to placebo across various studies. However, canagliflozin usage has led to higher amputation events in certain trials.
Keywords: amputations; diabetes; sodium-glucose cotransporter 2 inhibitors; SGLT-2 inhibitors; type 2 diabetes mellitus